1988
DOI: 10.1111/j.1365-2710.1988.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Liquid Chromatographic Analysis of Caffeine Concentrations in Plasma and Saliva

Abstract: A rapid high performance liquid chromatographic (HPLC) method for the analysis of caffeine in plasma and saliva is described. Samples of saliva and plasma were purified using zinc sulphate solution as protein precipitant. The supernatant was injected directly onto the column. The mobile phase consisted of ammonium acetate buffer:acetonitrile:methanol (82:15:3, v/v). Measurements were carried out at 254 nm. Acetanilide was used as the internal standard and analysis was completed in 10 min. No interference from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 7 publications
4
18
0
Order By: Relevance
“…Each subject provided a saliva sample 2.5 h before the first caffeine/placebo capsule, 5 min before bedtime, and 5 min after wake time. A rapid high-performance liquid chromatographic (HPLC) method was used for the analysis of caffeine in saliva (Alkaysi et al, 1988). The HPLC system consisted of a Spectra SYSTEM pump and a spectra SYSTEM UV detector (Thermoseparation Products Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Each subject provided a saliva sample 2.5 h before the first caffeine/placebo capsule, 5 min before bedtime, and 5 min after wake time. A rapid high-performance liquid chromatographic (HPLC) method was used for the analysis of caffeine in saliva (Alkaysi et al, 1988). The HPLC system consisted of a Spectra SYSTEM pump and a spectra SYSTEM UV detector (Thermoseparation Products Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that caffeine concentrations measured in saliva correlate highly with levels measured in blood (Alkaysi et al, 1988). Moreover, because plasma caffeine levels typically increase progressively during the day (due to intermittent consumption of caffeine beverages) and plateau by late afternoon or early evening, the best single-sample bioassay of daily caffeine intake is provided by samples obtained in the late afternoon (Lelo et al, 1986).…”
Section: Salivary Caffeinementioning
confidence: 98%
“…To check compliance with the prescribed caffeine regimen, participants provided a 5-ml sample of saliva at 17.00 h for every day of the 4-week program. Previous research has shown that caffeine concentrations measured in blood and saliva are highly correlated [27]. Moreover, because plasma caffeine levels typically increase progressively during the day (due to intermittent consumption of caffeine beverages) and plateau by late afternoon or early evening, the best single-sample bioassay of daily caffeine intake is provided by samples obtained in the late afternoon [28].…”
Section: Experimental Designmentioning
confidence: 99%